A new version of the results of Un–hypermetric spaces - Dehghan Nezhad, Akbar; Forough, Ahmadreza; Mirkov, Nikola; Radenović, Stojan (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The aim of this paper is to present the concept of a universal hypermetric space. An n-dimensional (n ≥ 2) hypermetric distance over an arbitrary non-empty set X is generalized. This hypermetric distance measures how separated all n points of the space are. The paper discusses the concept of completeness, with respect to this hypermetric as well as the fixed point theorem which play an important role in applied mathematics in a variety of fields. Methods: Standard proof based theoretical methods of the functional analysis are employed. Results: The concept of a universal hypermetric space is presented. The universal properties of hypermetric spaces are described. Conclusion: This new version of the results for Un-hypermetric spaces may have applications in various disciplines where the degree of clustering is sought for.